Reactive Oxygen Species Generation and Use of Antioxidants during In Vitro Maturation of Oocytes - Khazaei, Mozafar (Int J Fertil Steril, 2017)
In vitro maturation (IVM) is emerging as a popular technology at the forefront of fertility treatment and preservation. However, standard in vitro culture (IVC) conditions usually increase reactive oxygen species (ROS), which have been implicated as one of the major causes for reduced embryonic development. It is well-known that higher than physiological levels of ROS trigger granulosa cell apoptosis and thereby reduce the transfer of nutrients and survival factors to oocytes, which leads to apoptosis. ROS are neutralized by an elaborate defense system that consists of enzymatic and non-enzymatic antioxidants. The balance between ROS levels and antioxidants within IVM media are important for maintenance of oocytes that develop to the blastocyst stage. The effects of antioxidant supplementation of IVM media have been studied in various mammalian species. Therefore, this article reviews and summarizes the effects of ROS on oocyte quality and the use of antioxidant supplementations for IVM, in addition to its effects on maturation rates and further embryo development.